The Importance of the Organizational Characteristics of the Construction Network in the Development of the Building Materials Industry - Umida, Uzakova (Research Parks Publishers, 2023)
In this scientific article, the formation of a cluster at enterprises operating in the construction industry in the development of the building materials industry through which the existing problems for the development of the sector, ways to increase economic efficiency by organizing economical production of building materials, proposals and recommendations for ways to eliminate them are developed.